Implementation of a Sustainable Training System for Emergency in Vietnam - Kang, Sunjoo; Seo, Hyejin; Ho, Binh Duy; Nguyen, Phuong Thi Anh (Frontiers in Public Health, 2018)
Purpose: This study analyzed the project outcomes to share lessons regarding the development of an emergency medicine education system in Vietnam. Methods: Retrospective evaluation was implemented using project outcome indicators. Results: A total of 13 training courses were administered, with the collaboration of international experts in Korea and Vietnam. A total of 23 kinds of emergency medicine education equipment were purchased, and a basic life support and two advanced cardiac life support labs were remodeled to provide appropriate simulation training. Throughout the two years of the project, nine Vietnamese basic life support instructors were approved by the Korea Association of Cardiopulmonary Resuscitation under American Heart Association. Results of evaluation by Korean international development experts were, based on five criteria provided by the Development Assistance Committee of the Organization for Economic Co-operation and Development, were excellent. Success factors were identified as partnership, ownership, commitment, government support, and global networking. Conclusions: Project indicators were all accomplished and received an excellent evaluation by external experts. For sustainable success, healthcare policy and legal regulation to promote high-quality and safe service to the Vietnamese people are recommended.